The Dynamics of Gender Justice in the Agricultural Sector of Transmigration Areas in Lampung Province - Heni Widyawati; Hidayatullah, Muhammad Subkhi (Women, Education, and Social Welfare, 2025)
The issue of gender inequality in the agricultural sector continues to be a concern, especially in transmigration areas that have unique socio-economic and cultural characteristics. This research examines the gender dynamics experienced by women in the agricultural sector in transmigration areas of Lampung Province, with a focus on the forms of structural injustice that are still ongoing. The main objective of this research is to identify and analyse the practices of labelling, marginalization, subordination, violence and double burden experienced by women, and to explore their social implications in the context of regional development. This research uses a library research approach by analyzing various relevant literature sources, such as books, journals, research reports, and policy documents related to gender and transmigration. The results show that transmigrant women experience injustice in various interrelated forms, ranging from stereotyping of domestic roles to limited access to wages and decision-making. The implications of these findings point to the importance of more responsive gender-based policies and the need for integrated women's empowerment interventions. This research contributes to the literature on gender and agriculture, and opens space for further research with a wider range of areas and approaches.